2016
DOI: 10.1093/treephys/tpv146
|View full text |Cite
|
Sign up to set email alerts
|

Role of leaf hydraulic conductance in the regulation of stomatal conductance in almond and olive in response to water stress

Abstract: The decrease of stomatal conductance (gs) is one of the prime responses to water shortage and the main determinant of yield limitation in fruit trees. Understanding the mechanisms related to stomatal closure in response to imposed water stress is crucial for correct irrigation management. The loss of leaf hydraulic functioning is considered as one of the major factors triggering stomatal closure. Thus, we conducted an experiment to quantify the dehydration response of leaf hydraulic conductance (Kleaf) and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 52 publications
7
38
0
1
Order By: Relevance
“…have applied rigorous refinements of previous methods to this problem. Importantly, they confirm the dramatic decline of K leaf before turgor loss point and, following Hernandez-Santana et al (2016), demonstrate similar vulnerability using two different methods on the same species. They also used a recently developed vacuum method based on measuring leaves with severed minor veins to measure the leaf xylem hydraulic vulnerability (Scoffoni and Sack, 2015), and determined the outside-xylem hydraulic vulnerability by subtraction.…”
Section: Steep Leaf Responsesupporting
confidence: 67%
“…have applied rigorous refinements of previous methods to this problem. Importantly, they confirm the dramatic decline of K leaf before turgor loss point and, following Hernandez-Santana et al (2016), demonstrate similar vulnerability using two different methods on the same species. They also used a recently developed vacuum method based on measuring leaves with severed minor veins to measure the leaf xylem hydraulic vulnerability (Scoffoni and Sack, 2015), and determined the outside-xylem hydraulic vulnerability by subtraction.…”
Section: Steep Leaf Responsesupporting
confidence: 67%
“…Notably, the species in that study were far less drought tolerant than our Southern California species and thus may exhibit different stomatal behaviours. Further, the difference may arise from the estimation of water status at stomatal closure, which was alternatively measured in the dark (Burghardt & Riederer, ) or for illuminated leaves (this study); several studies have shown that stomata remain substantially open for illuminated leaves even to bulk leaf turgor loss (Guyot et al, ; Hernandez‐Santana, Rodriguez‐Dominguez, Fernández, & Diaz‐Espejo, ). Although our findings for loss of cell integrity or viability before stomatal closure necessitate reconsideration of some common ideas of stomatal protection, they are consistent with those of several recent studies that showed substantial reductions in leaf hydraulic conductance ( K leaf ) before stomata closed by 50% (Bartlett et al, ; Brodribb et al, ; Johnson, Woodruff, McCulloh, & Meinzer, ).…”
Section: Discussionmentioning
confidence: 97%
“…An explanation for the discrepancies between our findings regarding unchanged K shoot and those that report a decline in leaf hydraulic conductance at low levels of water stress in olive under field conditions (Torres‐Ruiz et al ., ; Hernandez‐Santana et al ., ) still needs to be elucidated. For instance, combinations of different hydraulic approaches, including leaf anatomical analyses, to quantify the outside‐xylem hydraulic conductance of the leaves and to localize where the main constrains to water flow occur, may help to make more progress on this question.…”
Section: Discussionmentioning
confidence: 99%